Approaches and indications in laparoscopic choledoscopy - Iulian Slavu; Raluca Tulin; Ileana Dima; Alexandru Dogaru; Florin Filipou; Bogdan Socea; Anca Monica Oprescu-Macovei; Adrian Tulin (Journal of Mind and Medical Sciences)
Objectives. Up to 20% of patients with biliary lithiasis have bile duct stones, which are asymptomatic in 50% of cases. The aim of the study was to evaluate the role of choledoscopy in extracting stones from the main bile ducts. Materials and Methods. This is a retrospective study (January 2014 - December 2024) on 2309 patients who underwent a laparoscopic cholecystectomy. Laparoscopic choledoscopy was performed in 32 cases. Of the 32 patients with complete clearance, none had residual common bile duct stones (CBDS) at 1 year postoperatively. Results. The ideal approach in our study was the transcystic approach, with the shortest hospital stays (mean 3 days) transcholedochal approach; it was only feasible in 7 patients. All patients had transcystic drainage that was removed after 10 days (mean operative time 105 min). The transcholedochal approach was demanding from a technical point of view. Primary ductal closure was performed in 5 patients. Ductal closure with transcystic drain was in 9 patients. A total of 14 patients had a T-tube and a longer operative time (on average 170 min). Conversion to open surgery was performed in 4 cases, due to difficult dissection at the level of the hepatic porta. Conclusions. LCBDE for previously documented or discovered CBDS during LC is a safe and feasible procedure. The technique is technically demanding, and requires advanced laparoscopic skills. Patient selection is very important, but the transcystic approach for LCBDE when possible is optimal.